FORMULATION AND IN VITRO EVALUATION OF MATRIX TABLETS OF METOCLOPRAMIDE HYDROCHLORIDE - JAYA, S.; S., DIVYA (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of present study was to formulate oral sustained release matrix tablet of metoclopramide hydrochloride and to evaluate the effect of varying concentrations of hydrophobic and hydrophilic polymers on drug release. Methods: Drug–excipients compatibility studies were carried out by using Fourier transform infrared spectroscopy (FTIR). The matrix tablets were prepared by direct compression technique using Xanthan gum and ethyl cellulose alone and in combination as release retardant. Dicalcium phosphate was used as diluent. The prepared matrix tablets were evaluated for their physicochemical parameters such as weight variation, hardness, friability, content uniformity and in vitro drug release studies were performed using USP-type II (paddle) dissolution apparatus. Results: Pre and post compression parameters were evaluated and all the parameters were found within the limit. The matrix tablets prepared with xanthan gum and combination of xanthan gum and ethyl cellulose were retarded the drug release upto 12 h. Ethyl cellulose alone could not control the drug release for 12 h. The Formulation with drug to xanthan gum (1:1.5), released 97.62 % of drug in 12 h. The kinetic treatment showed that the release of drug follows zero order kinetics (R 2=0.985). Korsmeyer and Peppas equation values of n were found to be in the range of 0.40-0.56, indicating that the drug release mechanism was diffusion. Conclusion: Matrix tablet is the simple, efficient and economic method to sustain the release of metoclopramide to prevent extrapyramidal side effects.